Pengembangan Karakter Siswa Melalui Kegiatan Ekstrakurikuler di SLTA Kota Banda Aceh - Munzahri (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Extracurricular activities are learning activities that are held outside of class hours which are arranged with the need for knowledge, development, guidance and habituation of students to have basic supporting knowledge. The purpose of this study was to determine the implementation of character development through religious extracurricular activities and to determine the supporting and inhibiting factors of character development through religious extracurricular activities in Banda Aceh City Senior High School. This research was conducted with a field study using a qualitative descriptive method. Data collection techniques were carried out through interviews and documentation. From the research conducted by the researcher, the results obtained are that the implementation of character development through religious extracurricular activities held by the Banda Aceh City Senior High School is praying together and reading yasin, zuhur prayer obligatory in congregation, reading and writing program of the Qur'an, activities Islamic holidays, sharing Friday programs. The supporting factors for character development through religious extracurricular activities include support from teachers and school principals as well as enthusiasm from school residents, and adequate facilities and infrastructure, while obstacles in these activities of course exist such as there are still some students who do not take part in these activities and also some facilities. inadequate infrastructure if there are larger activities such as isra' mi'raj and the commemoration of the Prophet's birthday.